Efektivitas Layanan Informasi dalam Memberikan Pendidikan Seks pada Siswa MTsN 5 Lima Puluh Kota - Hapzia, Alyatul; Rahmi, Alfi (Lembaga Yasin AlSys, 2025)
Sex education is essential from an early age to help children understand the functions of sexual organs, personal responsibility, the boundaries of what is permissible and forbidden, and to serve as a guide in preventing deviant sexual behavior. This study aims to determine students' level of understanding of sex education before and after receiving information services. The research employed a pre-experimental design using a one-group pretest-posttest model. The population consisted of seventh-grade students at MTsN 5 Lima Puluh Kota, with a sample of 25 students selected through purposive sampling. The research instrument was a sex education questionnaire that had been validated and tested for reliability, consisting of 15 valid statements with a reliability coefficient of 0.821, indicating the instrument was suitable as a measurement tool. Data analysis was conducted using the Wilcoxon test, which showed an Asymp. Sig (2-tailed) value of 0.000 (< 0.05), leading to the rejection of H₀ and acceptance of Hₐ. These results indicate a significant change in students' understanding after the delivery of the information service. The study concludes that information services are effective in enhancing the understanding of sex education among students at MTsN 5 Lima Puluh Kota. The implication is that information services can serve as an educational strategy to equip students with accurate knowledge to navigate the complexities of sexual development during adolescence.